Synthesis of geopolymer from spent FCC: Effect of SiO2/Al2O - J. J. Trochez; R. Mejía de Gutiérrez; J. Rivera; S. A. Bernal (Materiales de Construccion, 2015)
This paper assesses the feasibility of using a spent fluid catalytic cracking catalyst (SFCC) as precursor for the production of geopolymers. The mechanical and structural characterization of alkali-activated SFCC binders formulated with different overall (activator + solid precursor) SiO2/Al2O3 and Na2O/SiO2 molar ratios are reported. Formation of an aluminosilicate ‘geopolymer’ gel is observed under all conditions of activation used, along with formation of zeolites. Increased SiO2/Al2O3 induces the formation of geopolymers with reduced mechanical strength, for all the Na2O/SiO2 ratios assessed, which is associated with excess silicate species supplied by the activator. This is least significant at increased alkalinity conditions (higher Na2O/SiO2 ratios), as larger extents of reaction of the spent catalyst are achieved. SiO2/Al2O3 and Na2O/SiO2 ratios of 2.4 and 0.25, respectively, promote the highest compressive strength (67 MPa). This study elucidates the great potential of using SFCC as precursor to produce sustainable ceramic-like materials via alkali-activation.